The Impact of Career Pathing Practices on Job Satisfaction of Employees at BIR Document Processing Division in RR4 - PAMPANGA - Rojas, John Benedict C.; Roque, John Francis D.; Unico, Maricris G.; Abante, Marmelo V. (International Journal of Entrepreneurship and Sustainability Studies, 2024)
This research investigates the impact of career pathing on job satisfaction among employees of the Bureau of Internal Revenue (BIR) Document Processing Division in RR4, Pampanga. Career pathing is a strategic framework designed to outline clear advancement trajectories and to align skill development opportunities with promotions. This study uses a descriptive correlational design, incorporating a survey of 73 employees to assess the level of career pathing implementation and its relationship with job satisfaction. Data were analyzed using statistical methods to determine the strength of the correlation between career pathing practices and job satisfaction. Findings suggest that job promotions play a significant role in enhancing motivation and commitment, supporting the existing literature that shows a positive correlation between perceived advancement opportunities and job satisfaction. In the context of the Philippines, perceptions of career pathing are pivotal to job satisfaction because they influence workplace relationships and organizational culture. However, bureaucratic structures in government agencies can hinder career progression, leading to low employee morale and productivity. This research provides insights into the effectiveness of promotion criteria and transparency in BIR career pathing practices. The findings are expected to offer recommendations that enhance employee satisfaction and improve organizational stability. By contributing to the understanding of how career pathing can be optimized, this study seeks to help public sector organizations better meet their employees’ career aspirations.